DETERMINING THE STUDENT TEACHERS’ PERCEPTION ON THE SENSE OF RESPONSIBILITY - Sedef SÜER (Fırat University, 2019)
In this study, student teachers’ perceptions on their sense of responsibility in their preservice training process is tried to be determined in respect of that teachers are generally taken as a model by upcoming generations and they generally play an important role in educating the new generations in a way that they can have good level of responsibility. In line with this purpose, the sense of responsibility of the student teachers studying at Ziya Gökalp Education Faculty of Dicle University is tried to be determined via Likert 5 Point Scale developed for this purpose. The scale is applied to total 413 students teachers studying at 4. and 5. grades randomly sampled from the different teacher education departments that give 4 or 5 years education. In the light of collected data, the student teachers have been determined to have high level of responsibility and the perceptions of student teachers on the sense of responsibility have been determined to differ significantly in terms of sex and their satisfaction degree with the deparment they are studying variables.